The Role of Communist Women in the Adoption of the Personal Status Law No. 188 of 1959 - Al –Saidi , Raja Karim Jihad; Al-Hajjaj, Furat Abdulhassan Kazim (Journal of Posthumanism, 2025)
Communist women contributed by virtue of their affiliation with the League for the Defense of Iraqi Women's Rights ( )IWRI) and by virtue of their position in the government, especially after the appointment of Dr. Naziha Al-Dulaimi( ) as Minister of Municipalities on July 13, 1959, in the adoption of the Personal Status Law, which is the first progressive law in Iraq and the Arab region as a whole that guarantees women part of their civil and political rights. The research was divided into two axes, the first axis dealt with the role of the League for the Defense of Women's Rights in issuing the Personal Status Law No. 188 of 1959. The second axis dealt with the position of clerics and political forces opposed to the issuance of the Personal Status Law.